2002
DOI: 10.1007/bf03345096
|View full text |Cite
|
Sign up to set email alerts
|

EP1572: A novel peptido-mimetic GH secretagogue with potent and selective GH-releasing activity in man

Abstract: EP1572 UMV1843 [Aib-DTrp-DgTrp-CHO]) is a new peptido-mimetic GH secretagogue (GHS) showing binding potency to the GHS-receptor in animal and human tissues similar to that of ghrelin and peptidyl GHS. EP1572 induces marked GH increase after s.c. administration in neonatal rats. Preliminary data in 2 normal young men show that: 1) acute i.v. EP1572 administration (1.0 microg/kg) induces strong and selective increase of GH levels; 2) single oral EP1572 administration strongly and reproducibly increases GH levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 8 publications
1
46
1
Order By: Relevance
“…[8][9][10] All attempts to replace the Aib residue resulted in less potent compounds, indicating the significance of this residue for the stimulation of GH secretion. Recently, we reported that 1,2,4-triazole was a good scaffold to obtain potent GHS-R1a ligands of the ghrelin receptor, leading to agonists, partial agonists, or antagonists.…”
Section: Chemistrymentioning
confidence: 99%
“…[8][9][10] All attempts to replace the Aib residue resulted in less potent compounds, indicating the significance of this residue for the stimulation of GH secretion. Recently, we reported that 1,2,4-triazole was a good scaffold to obtain potent GHS-R1a ligands of the ghrelin receptor, leading to agonists, partial agonists, or antagonists.…”
Section: Chemistrymentioning
confidence: 99%
“…BIM-28131, a small peptide ghrelin agonist, and BIM-28163, a full-length ghrelin analog antagonist were used in some studies on hypothalamic actions of ghrelin [228]. Also, some peptidomimetics have been produced including the pseudotripeptide EP01572 (H-Aib-(D)-Trp-(D)-gTrp-formyl) with increased stability and oral bioavailability [229] even in human [230], and JMV 1843 [231] shown in (Fig. 5A).…”
Section: Ghrelinmentioning
confidence: 99%
“…By counting neurons, we found a better preservation of cellularity in regions in which damage was more pronounced, such as the hilus of dentate gyrus and the layer III of medial entorhinal cortex, only in rats treated with JMV-1843. The beneficial findings observed with JMV-1843 administration were probably related to the advantageous pharmacokinetics of this drug when compared to ghrelin [79,80].…”
Section: Is Vascular Protection An Affordable Goal For Treatment Of Smentioning
confidence: 90%